Indonesian Islam in the Context of Global Islamic Fundamentalism: A Study of Radicalization and Counter-Radicalization - Md Shodiq; Ethan Tan; lucas wong (Yayasan Adra Karima Hubbi, 2025)
This study examines the complex dynamics of Indonesian Islam amidst the rise of global Islamic fundamentalism, focusing specifically on processes of radicalization and counter-radicalization within the archipelago. Indonesia, as the world’s largest Muslim-majority nation, presents a unique case due to its historically pluralistic and moderate religious landscape, which now faces increasing pressure from extremist ideologies. The primary objective of this research is to identify the key drivers of radicalization among Indonesian Muslims and to critically assess the effectiveness of existing counter-radicalization strategies implemented by the government and civil society organizations. Utilizing a mixed-methods approach, this study combines a quantitative analysis of survey data from 500 university students and religious leaders across Java and Sumatra with qualitative in-depth interviews. The qualitative component involved 30 participants, including former extremists, religious scholars, and policymakers, providing nuanced insights into their experiences and perspectives on radicalization and deradicalization. Results indicate that socio-economic grievances, misinterpretations of religious texts, and online propaganda are significant factors contributing to radicalization, particularly among younger demographics. In conclusion, Indonesian Islam demonstrates significant resilience against fundamentalist encroachment, largely due to its strong civil society and established moderate religious organizations.